Settlement of the Bronze Age and the Hallstatt Periods at Chrząstów Folwarczy 1 Parzęczew Commune County Zgierz, Łódź Province Poland : The A2 Motorway, Contents - Maik, Jerzy - Red. (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2002)
p. 5
Keywords: reports of archaeological works -- Poland; review of archaeological finds

Wykopaliska monet starożytnych i średniowiecznych (Polskie Towarzystwo Prehistoryczne, 1924)
29 cm
Keywords: antiquity-Middle Ages -- Poland; ancient-medieval coins; review of archaeological finds

Introduction - Maik, Jerzy (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2002)
P. 7-10 : ill.
Keywords: reports of archaeological works -- Poland; review of archaeological finds; Chrzęstów Folwarczy, Parzęczew commune (Poland)

Ślady osadnictwa z epoki kamienia - Herman, Radosław (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2002)
P. 13-15 : ill.
Keywords: Stone Age -- Poland; Stone Age settlement; review of archaeological finds; Chrząstów Folwarczy (Poland)

Nowe znaleziska w powiecie rawickim - Jażdżewski, Konrad (1908–1985) (Polskie Towarzystwo Prehistoryczne, 1927)
ill. ; 29 cm
Keywords: Mesolithic-early Middle Ages -- Poland; archaeological sites -- Poland; review of archaeological finds; Rawicz, wielkopolskie voivodeship-region (Poland)

Materjały do pradziejów Górnego Śląska - Kostrzewski, Józef (1885–1969) (Polskie Towarzystwo Prehistoryczne, 1928)
ill. ; 29 cm
Keywords: Stone Age-early Middle Ages -- Poland; Stone Age-early medieval cultures; review of archaeological finds

Sprawozdania Archeologiczne T. 44 (1992), Omówienia i recenzje - Blajer, Wojciech. Reviewer (Polska Akademia Nauk. Instytut Archeologii i Etnologii, 1992)
Richard Bradley, The Passage of Arms, Cambridge 1990, XVI + 234 ss.
P. 299-306 ; 25 cm
Bibliography p. 306
Keywords: prehistory-Roman period; prehistoric-Roman period hoards; to bring offerings; review of archaeological finds

Sprawozdania Archeologiczne T. 54 (2002), Omówienia i recenzje - Kadrow, Sławomir (1956– ). Reviewer (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2002)
Klaus-Peter Wechler, Studien zum Neolithicum der osteuropäischen Steppe, Deutsches Archäologisches Institut, Eurasien-Abteilung (= Archäologie in Eurasien 12), Mainz 2001, 372 strony, w tym: 57 ilustracj i 30 tabel oraz 57 tablic rysunkowych poza tekstem
P. 207-211 ; 25 cm
Bibliography p. 211
Keywords: Neolithic -- eastern Europe; Neolithic settlement; Neolithic cultures; material culture of the Neolithic; review of archaeological finds

Sprawozdania Archeologiczne T. 39 (1988), Omówienia i recenzje - Gurba, Jan (1929– ). Reviewer (Zakład Narodowy im. Ossolińskich, 1988)
I. S. Vinokur, A. F. Hucał, S. I. Penjak, B. O. Timoščuk, V. I. Jakubovśkyj, Dovidnyk z archeołohii Ukrainy. Chmielnićka, Zakarpatśka obłasti, Kyiv 1984, 222 ss.
P. 369-370 ; 25 cm
Bibliographical footnotes
Keywords: archaeological informant -- Ukraine; archaeology of Ukraine; review of archaeological sites -- Ukraine; review of archaeological finds

Zabytki kultury ceramiki sznurowej z Markowej, woj. Rzeszów - Podgórska-Czopek, Joanna (Zakład Narodowy im. Ossolińskich, 1985)
P. 51-54 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Neolithic -- Poland; Corded Ware culture; material culture of the Corded Ware culture; review of archaeological finds; Markowa (Poland)

Z badań powierzchniowych na Spiszu Polskim - Parczewski, Michał (1946– ) (Zakład Narodowy im. Ossolińskich, 1972)
P. 295-297 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Stone Age -- Poland; early Middle Ages -- Poland; surface survey; review of archaeological finds; Spisz (Poland)

Badania rozpoznawcze wokół torfowiska Łąki Staświńskie, woj. Suwałki - Kempisty, Elżbieta (1934–1985) (Zakład Narodowy im. Ossolińskich, 1986)
P. 57-76 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Stone Age -- Poland; test excavations; Stone Age peat-bog sites; review of archaeological finds; Łąki Staświńskie (Poland)

Deutschlands Urgeschichte - Strasser, Karl Theodor (1888–1936) (M. Diesterweg, 1935)
4. Aufl. - [4th ed.]
[4], 121 p. : ill. ; 23 cm
Index of persons and places
Bibliography p. 117-119
Keywords: prehistory-early Middle Ages -- Germany; archaeological cultures of Germany; review of archaeological finds

Sprawozdania Archeologiczne T. 47 (1995), Omówienia i recenzje - Zoll-Adamikowa, Helena (1931–2000). Reviewer (Polska Akademia Nauk. Instytut Archeologii i Etnologii, 1995)
Wamers Egon, Die frühmittelalterlichen Lesefunde aus der Löhrstraße (Baustelle Hilton II) in Mainz, 1994, 267 ss., 115 rycin w tekście, aneksy: Peter Berghaus i Christian Stoess; w serii Mainzer Archäologische Schriften, t. 1
P. 300-303 ; 25 cm
Bibliographical footnotes
Keywords: early Middle Ages -- Germany; material culture of the early Middle Ages; review of archaeological finds; Mainz (Germany)

Sprawozdania Archeologiczne T. 58 (2006), Reviews - Dzbyński, Aleksander (1972– ). Reviewer (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2006)
J. Czebreszuk, J. Müller (Hrsg.), Bruszczewo. Ausgrabungen und Forschungen in einer prähistorischen Siedlungskammer Grosspolens. Teil I, Forschungsstand - Erste Ergebnisse - Das östliche Feuchtbodenareal (= Studien zur Archäologie in Ostmitteleuropa 2). Poznań-Kiel-Rahden (Westf.) 2004, 330 Seiten
J. Czebreszuk, J. Müller (red.), Bruszczewo. Badania mikroregionu osadniczego z terenu Wielkopolski. Część I, Stan badań - Pierwsze wyniki - Wschodnia, torfowa część stanowiska (= Studien zur Archäologie in Ostmitteleuropa 2). Poznań-Kiel-Rahden (westf.) 2004, 330 str.
P. 573-581 ; 25 cm
Bibliography p. 577
Text paralel in German and Polish
Keywords: Bronze Age -- Poland; Bronze Age settlement; material culture of the Bronze Age; review of archaeological finds; Bruszczewo (Poland)

Wielokulturowe stanowisko 1 w Dziekanowicach, woj. świętokrzyskie - Jaśkowiak, Paweł (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2001)
P. 111-163, [1] leaf of photos : ill., tables ; 25 cm
English summary
Bibliography p. 160-161
Keywords: Neolithic -- Poland; multicultural archaeological sites; Neolithic settlement; Neolithic cultures; review of archaeological finds; Dziekanowice (Poland)

Przegląd Archeologiczny : organ c. k. Konserwatoryi Pomników i Towarzystwa Archeologicznego Krajowego we Lwowie Z. 4 (1888) - Towarzystwo Archeologiczne Krajowe (Lwów) (Towarzystwo Archeologiczne Krajowe, 1882)
Yearbook
25 cm
Keywords: archaeology -- journals; history -- journals; review of archaeological finds -- journals; archival sources -- journals

Przegląd Archeologiczny : organ c. k. Konserwatoryi Pomników i Towarzystwa Archeologicznego Krajowego we Lwowie Z. 1 (1882) - Towarzystwo Archeologiczne Krajowe (Lwów) (Towarzystwo Archeologiczne Krajowe, 1882)
Yearbook
25 cm
Keywords: archaeology -- journals; history -- journals; review of archaeological finds -- journals; archival sources -- journals

Przegląd Archeologiczny : organ c. k. Konserwatoryi Pomników i Towarzystwa Archeologicznego Krajowego we Lwowie Z. 2 (1883) - Towarzystwo Archeologiczne Krajowe (Lwów) (Towarzystwo Archeologiczne Krajowe, 1882)
Yearbook
25 cm
Keywords: archaeology -- journals; history -- journals; review of archaeological finds -- journals; archival sources -- journals

Przegląd Archeologiczny : organ c. k. Konserwatoryi Pomników i Towarzystwa Archeologicznego Krajowego we Lwowie Z. 3 (1883) - Towarzystwo Archeologiczne Krajowe (Lwów) (Towarzystwo Archeologiczne Krajowe, 1882)
Yearbook
25 cm
Keywords: archaeology -- journals; history -- journals; review of archaeological finds -- journals; archival sources -- journals

Materyjały Antropologiczno - Archeologiczne z. 1 (1877) - Akademia Umiejętności (Kraków). Komisja Archeologiczna; Akademia Umiejętności (Kraków). Komisja Antropologiczna (Akademia Umiejętności, 1877)
ill. ; 23 cm
Description based on: Z. 1 (1877)
Keywords: physical anthropology; review of archaeological finds; central-eastern Europe; regional archaeological research -- south-eastern Europe

Nowe znaleziska ze starych wykopalisk : zabytki z okresu wpływów rzymskich w zbiorach Muzeum w Elblągu - Natuniewicz-Sekuła, Magdalena (Stowarzyszenie Naukowe Archeologów Polskich, 1999)
P. 115-131 : ill. ; 30 cm
Bibliography p. 122-124
Keywords: Muzeum w Elblągu [Museum in Elbląg] (Elbląg, Poland); archaeological collections -- Poland; Roman period -- Poland; review of archaeological finds

Polish-Macedonian Excavations at Negotino Gradište. Preliminary Report 2009–2015 - Brillowski, Wojciech; Koperkiewicz, Arkadiusz; Sanev, Goran; Sekunda, Nicholas (Wydawnictwo IAE PAN, 2017)
Negotino Gradište has been systematically excavated by a multi-national team since 2009. The site goes as far back as the 5th century BC. The earliest coin found at the site so far is a tetrobol of Acanthus, dating to ca. 525– 470 BC. Fourth-century, Hellenistic, and Roman levels have been excavated so far. There is a hiatus in settlement between the Late Hellenistic and Augustan periods. The site was deserted in the early 2nd century AD. Probably in the reign of Arcadius (AD 383–408) it was roughly fortified as a refuge settlement
ill. ; 31 cm
Keywords: antiquity -- Republic of Macedonia; Negotino Gradište (Republic of Macedonia); Polish-Macedonian excavations; ancient settlement; review of archaeological finds

Cmentarzysko z kulturą rzymską w Ciążeniu, w pow. słupeckim (woj. łódzkie) - Zakrzewski, Zygmunt (1867–1951) (Polskie Towarzystwo Prehistoryczne, 1923)
ill. ; 29 cm
Keywords: Roman period -- Poland; Roman period cemeteries -- Poland; Roman period grave goods; review of archaeological finds; Ciążeń, Lądek commune (Poland)

Cmentarzysko kultury złockiej "nad Wawrem" w Złotej - Krzak, Zygmunt (1933– ) (Zakład Narodowy im. Ossolińskich ;, 1970)
203 p., [1] folded leaf : ill. ; 24 cm
Bibliographical footnotes
English summary
Keywords: Neolithic -- Poland; Złota culture cemeteries; Złota culture graves -- catalogue; Złota culture grave goods; review of archaeological finds; Złota, com. Samborzec (Poland)